Applying GST to Understand and Contextualize Bullying: A Conjunctive Analysis of Case Configurations - Paez, Gabriel R. (Journal of interpersonal violence, 2023)
Drawing from Agnew’s general strain theory, this study examines whether certain risk factors have a consistent effect across different situational contexts that characterize bullying perpetration. A conjunctive analysis of case configurations was conducted to examine and identify situational factors that increase adolescents’ risks for bullying perpetration using data from the 2019 Minnesota Student Survey. Results from a sample of 166,176 U.S. adolescents show that (1) incidents of traditional bullying perpetration cluster significantly among dominant situational profiles; (2) students most likely to be bullies experience victimization, but students least likely to bully their peers rarely experience bullying victimization; and (3) being a victim of traditional bullying can increase the chances of traditional bullying perpetration in some situational contexts, but can have almost no influence on perpetration in other contexts. Current findings are discussed considering existing bullying scholarship and recommendations for policy and future areas of research are presented.